Increasing Causal Effects of El Niño–Southern Oscillation on the Future Carbon Cycle of Terrestrial Ecosystems. Issue 24 (17th December 2021) - Le, Thanh; Ha, Kyung‐Ja; Bae, Deg‐Hyo
Abstract: Here we examine the causal effects of El Niño–Southern Oscillation (ENSO) on the global carbon cycle over historical and future periods utilizing datasets from the Coupled Modeling Intercomparison Project Phase 6 models. Our results show that ENSO exhibits impact on terrestrial carbon fluxes and carbon storage over numerous regions of Asia, Oceania, and America. High consensus is found between models for the influences of ENSO over these regions. The results demonstrate that the effects of ENSO on carbon cycling over subtropics and high‐latitude regions may be more significant than previously understood. In historical simulation, the regions affected by ENSO account for approximately 8.5% land‐area and this proportion rises to approximately 11.7% in the future simulation, indicating an increase in ENSO influences on the gross primary productivity of terrestrial ecosystems. In addition, the results emphasize stronger response of seasonal carbon stocks to ENSO compared to that of seasonal carbon fluxes. Plain Language Summary: The global carbon cycle is an essential component of the Earth climate system. However, there is uncertainty in the response of future carbon cycling to El Niño–Southern Oscillation (ENSO) variations. Under warming environment and anthropogenic impacts, further understanding of ENSO and carbon cycle connections is important to accurately estimate future climate change and extremes. In the present study, we examine the causal effects of ENSO on the global carbon cycle over the future period 2015–2100 utilizing datasets from climate model simulations. Our results show that ENSO exhibits impact on carbon cycling over numerous regions of Asia, Oceania, and America. The results underscore that the impacts of ENSO on carbon cycling over subtropical and high‐latitude regions may be more significant than previously understood. We conclude that the future projections show an increase in ENSO influences on terrestrial carbon cycle compared to the historical period 1915–2000. In historical simulation, the regions with significant ENSO effects on gross primary productivity account for 8.5% land‐area and this proportion rises to 11.7% in the future simulation. This work might contribute to the forthcoming adaptation of global change and carbon neutrality policy. Key Points: El Niño–Southern Oscillation (ENSO) exhibits causal impact on carbon fluxes and terrestrial carbon storage over numerous regions of Asia, Oceania, and America Projections over the future period show an increase in land‐area of regions affected by ENSO compared to the historical period The results emphasize that the response of seasonal carbon stocks to ENSO is stronger compared to the response of seasonal carbon fluxes